Calcium-dependent protein kinases as central hubs in plant abiotic stress signaling: mechanisms and prospects for crop improvement - Azupio, Samuel; Wang, Yu; Obeng, Joshua; Issah, Abdul Kadir; Chu, Jing; Zhang, Hongmei; Xie, Qing; Jiang, Xingyu (Frontiers in Plant Science, 2026)
Calcium-dependent protein kinases (CDPKs) are key Ca²+ sensors that decode stress-induced calcium signatures through substrate phosphorylation, ROS regulation, kinase cross-talk, and precise spatiotemporal activity, playing a central role in orchestrating plant responses to abiotic stress. This review systematically examines the central role of CDPKs in mediating plant tolerance to drought, salinity, and extreme temperatures. It highlights how CDPKs regulate key processes such as stomatal closure, ion homeostasis, osmotic balance, antioxidant defense, and gene expression through the phosphorylation of transcription factors, ion channels, and metabolic enzymes. Moreover, it discusses the functional redundancy and specificity within large CDPKs gene families, which enable precise responses to specific stresses. Furthermore, the review explores the critical cross-talk between CDPKs signaling networks and phytohormone pathways, particularly abscisic acid (ABA), and their integration with reactive oxygen species (ROS) and MAPK signaling cascades. Recent advances demonstrating the potential of manipulating specific CDPKs isoforms to enhance multi-stress resilience in transgenic plants are also summarized. By synthesizing current knowledge, this review provides insights into the molecular mechanisms of CDPKs-mediated stress adaptation. It identifies future research directions for developing climate-resilient crops through targeted genetic engineering of CDPKs signaling pathways.